2005
DOI: 10.1063/1.1999607
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of TiO2 nanoparticles on the Au(111) surface

Abstract: The growth of titanium oxide nanoparticles on reconstructed Au(111) surfaces was investigated by scanning tunneling microscopy and X-ray photoelectron spectroscopy. Ti was deposited by physical vapor deposition at 300 K. Regular arrays of titanium nanoparticles form by preferential nucleation of Ti at the elbow sites of the herringbone reconstruction. Titanium oxide clusters were synthesized by subsequent exposure to O 2 at 300 K. Two-and three-dimensional titanium oxide nanocrystallites form during annealing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
69
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 29 publications
15
69
2
Order By: Relevance
“…Also the "inverse system" TiO x /Au(111) has been observed to show an effective catalytic activity in promoting the water-gas shift (WGS) reaction [10], thus encouraging experimental work on the synthesis and characterization of TiO x structures supported by the Au(111) surface. After the oxidation of Ti clusters evaporated on Au(111), the formation of geometrically well-defined TiO 2 crystallites with triangular or hexagonal shape was reported by Biener et al [11] and Potapenko et al [12]. Hexagonal TiO x nanoparticles were also observed by Lauwaet et al [13] who revealed a semiconducting n-type character.…”
Section: Introductionmentioning
confidence: 82%
“…Also the "inverse system" TiO x /Au(111) has been observed to show an effective catalytic activity in promoting the water-gas shift (WGS) reaction [10], thus encouraging experimental work on the synthesis and characterization of TiO x structures supported by the Au(111) surface. After the oxidation of Ti clusters evaporated on Au(111), the formation of geometrically well-defined TiO 2 crystallites with triangular or hexagonal shape was reported by Biener et al [11] and Potapenko et al [12]. Hexagonal TiO x nanoparticles were also observed by Lauwaet et al [13] who revealed a semiconducting n-type character.…”
Section: Introductionmentioning
confidence: 82%
“…The component labeled "1-2" is related to components "1" and "2" in the Ti 2p 3/2 spectra and component "3" in the O 1s appears in concomitance with "3" in the Ti 2p 3/2 . Component "4" is needed to obtain a satisfactory fit of the O 1s spectra and its origin is uncertain [34][35][36].…”
Section: Electronic Structure Of Tio 2 (B)(001) On Au(111)mentioning
confidence: 99%
“…Metal oxide nanoparticles, represented by titanium dioxide (TiO 2 ), is of great technological importance in the field of heterogeneous catalysis for catalytic support of a wide variety of metals (Biener et al, 2005). The most important effects of TiO 2 compounds on plants are enhancement of the yield of various crops (~10-20%); an improvement of some essential element contents in plant tissues; an increase in the peroxidase, catalase, and nitrate reductase activities in plant tissues; and an enhancement of the chlorophyll content in paprika (Capsicum anuum L.) and green alga (Chlorella pyrenoidosa) (Hruby et al, 2002).…”
Section: Discussionmentioning
confidence: 99%